Pengembangan Pendekatan Pembelajaran Mendalam Berbasis Media Flashcard Pada Materi Bulutangkis Siswa Sekolah Dasar - Agus Satria; Hartati; Herri Yusfi; Iyakrus; Reza Resah Pratama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop a flashcard-based in-depth learning approach to improve badminton skills in 5th grade elementary school students. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The subjects of this study were SDN 3 Kasmaran as the experimental class and SDN 1 Kasmaran as the control class. The measurement instrument used the Games Performance Assessment Instrument (GPAI). This study was validated by 3 experts. 2 media experts and 1 material expert validated the flashcard media to have a validity level of 93.25% (very valid). The practicality test of the flashcard media reached 96.68% (very practical). The results of the normality test for the posttest scores of the experimental class and the control class were 0.889> 0.05, the homogeneity test was sig. 0.525 > 0.05 The N-gain test result is 0.4389 and the independent sample t test is 0.029 < 0.05. From the results of the study, it can be concluded that the development of an in-depth learning approach based on flashcard media is valid, practical, and effective in improving the badminton skills of 5th grade elementary school students. Keywords: badminton; Deep learning approach; flashcard